How do you differentiate H(x)=(x+x^-1)^3? Calculus Basic Differentiation Rules Power Rule 1 Answer Salvatore I. Nov 27, 2016 H'(x)=3(x^2+1-x^(-2)-x^(-4)) Explanation: H'(x)=3(x+x^(-1))^2*(1-x^(-2)) H'(x)=3(x^2+2+x^(-2))*(1-x^(-2)) H'(x)=3(x^2+2+x^(-2)-1-2x^(-2)-x^(-4)) Answer link Related questions How do you find the derivative of a polynomial? How do you find the derivative of y =1/sqrt(x)? How do you find the derivative of y =4/sqrt(x)? How do you find the derivative of y =sqrt(2x)? How do you find the derivative of y =sqrt(3x)? How do you find the derivative of y =sqrt(x)? How do you find the derivative of y =sqrt(x) using the definition of derivative? How do you find the derivative of y =sqrt(3x+1)? How do you find the derivative of y =sqrt(9-x)? How do you find the derivative of y =sqrt(x-1)? See all questions in Power Rule Impact of this question 7853 views around the world You can reuse this answer Creative Commons License